Design and fabrication of a 3D-printed acoustic levitator - Ng, Ka Lam (Nanyang Technological University, 2023)
Acoustic levitation is a technology that has numerous applications in fields such as material science, biology, chemistry, and pharmaceuticals. Acoustic levitation is the method of suspending objects or liquids in mid-air by using air pressure formed from ultrasonic sound waves, without the need for physical contact. This report describes the design and fabrication of an acoustic levitation device capable of two-dimensional manipulation and potential for three-dimensional manipulation of objects. The device uses a transducer array and control system to create standing wave patterns, which are used to levitate and manipulate objects in three dimensions using phase changing. The report presents the design and fabrication process, as well as the experimental testing, results and acoustic potential field plots of the device. The results demonstrate the potential of acoustic levitation to have precise control and manipulation of particles. This report contributes to the existing research on acoustic levitation and highlights the potential of this technology for 3D manipulation of particles within the acoustic levitation field.